Kinematic and Functional Gait Changes After the Utilization of a Foot Drop Stimulator in Pediatrics - Karunakaran, Kiran K.; Pilkar, Rakesh; Ehrenberg, Naphtaly; Bentley, Katherine S.; Cheng, JenFu; Nolan, Karen J. (Frontiers in Neuroscience, 2019)
Foot drop is one of the most common secondary conditions associated with hemiplegia post stroke and cerebral palsy (CP) in children, and is characterized by the inability to lift the foot (dorsiflexion) about the ankle. This investigation focuses on children and adolescents diagnosed with brain injury and aims to evaluate the orthotic and therapeutic effects due to continuous use of a foot drop stimulator (FDS). Seven children (10 ± 3.89 years) with foot drop and hemiplegia secondary to brain injury (stroke or CP) were evaluated at baseline and after 3 months of FDS usage during community ambulation. Primary outcome measures included using mechanistic (joint kinematics, toe displacement, temporal-spatial asymmetry), and functional gait parameters (speed, step length, time) to evaluate the orthotic and therapeutic effects. There was a significant correlation between spatial asymmetry and speed without FDS at 3 months (r=0.76, p<.05, df =5) and no correlation between temporal asymmetry and speed for all conditions. The results show orthotic effects including significant increase in toe displacement (p<.025 N=7) during the swing phase of gait while using the FDS. A positive correlation exists between toe displacement and speed (with FDS at 3 months: r= 0.62, p>0.05, without FDS at 3 months: r= 0.44, p>0.05). The results indicate an orthotic effect of increased dorsiflexion and toe displacement during swing with the use of the FDS in children with hemiplegia. Further, the study suggests that there could be a potential long-term effect of increased dorsiflexion during swing with continuous use of FDS.